A review of theories on the Laestadian rørelse: on the academic construction of something extraordinary and exotic. (2nd January 2017) - Andreassen, Bengt-Ove
ABSTRACT: An ecstatic phenomenon usually labelled with the emic term rørelse (in English literally stirrings, motions or movement) has been central in the description and theoretical interpretation of the Laestadian Christian religious movement in northern Fennoscandia. The article considers two tendencies in the scholarly discussion. Firstly, how the discussion relies on descriptions of the rørelse derived from an evolutionary research paradigm applied to the Sami people during the late 1800s and the early 1900s, and secondly, how theories concerning the rørelse have been used in ideologically laden arguments to map the Laestadian movement as a specific Sami Christian revival. This has implied that the rørelse has been a pillar in arguments regarding the continuity of Sami religion ( noaidavoutna ) in the Laestadian movement.